2017
DOI: 10.1189/jlb.3a0716-300rr
|View full text |Cite
|
Sign up to set email alerts
|

Different dynamics of NLRP3 inflammasome-mediated IL-1β production in GM-CSF– and M-CSF–differentiated human macrophages

Abstract: IL-1b is a "master" cytokine regulating a wide variety of physiologic and immunologic processes. The most frequently studied models for NLRP3 inflammasomemediated IL-1b production are the macrophages; however, depending on their microenvironment, they can develop into functionally different cells. Several protocols have been developed to model the diversity of these cells in vitro. Here, we report for the first time, to our knowledge, a comparative study about the dynamics and molecular mechanisms of NLRP3 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
4
19
0
1
Order By: Relevance
“…Because the functional effects of curcumin and GG6 could not be tested using flow cytometry, we measured IL-1 β release by LPS-stimulated macrophages (see also [ 13 ]). Basal IL-1 β release by CSF-1-differentiated macrophages in the absence of inflammasome activator was barely detectable by ELISA (data not shown), consistent with recent studies [ 34 ]. Stimulation with LPS for 24 h significantly increased the release of IL-1 β into the medium (39.5 ± 14.8 pg/ml, n = 3; Figure 8 ).…”
Section: Resultssupporting
confidence: 91%
“…Because the functional effects of curcumin and GG6 could not be tested using flow cytometry, we measured IL-1 β release by LPS-stimulated macrophages (see also [ 13 ]). Basal IL-1 β release by CSF-1-differentiated macrophages in the absence of inflammasome activator was barely detectable by ELISA (data not shown), consistent with recent studies [ 34 ]. Stimulation with LPS for 24 h significantly increased the release of IL-1 β into the medium (39.5 ± 14.8 pg/ml, n = 3; Figure 8 ).…”
Section: Resultssupporting
confidence: 91%
“…As a master regulator of inflammation, IL-1β bioactivity fundamentally affects atherosclerosis as discussed already. A very recent study has revealed some stark, CSF-dependent differences in how and when IL-1β is produced by human MOs, which have implications for atherosclerosis research in vitro (Budai et al, 2017 ). In it, both GM-CSF and M-CSF-derived MOs release similar amounts of IL-1β, yet the release kinetics are dissimilar.…”
Section: Fundamental Differences In the Experimental Approaches Used mentioning
confidence: 99%
“…In it, both GM-CSF and M-CSF-derived MOs release similar amounts of IL-1β, yet the release kinetics are dissimilar. M-CSF-differentiated MOs stimulated with LPS and either ATP or nigericin release a high concentration of IL-1β after just 2 h, which declines substantially after 6 h, returning to baseline levels after 12 h (Budai et al, 2017 ). By contrast, when GM-CSF was used, IL-1β release was more gradual, peaking between 6 and 24 h yet continuing to remain well above baseline at this latter time point.…”
Section: Fundamental Differences In the Experimental Approaches Used mentioning
confidence: 99%
See 1 more Smart Citation
“…Az így aktivált gyulladásos kaszkád során a DC-k mellett a macrophagok, synovialis fibroblastok, hízósejtek és neutrophil granulocyták is aktiválódnak. A különböző sejtek által termelt gyulladásos mediátorok közül kiemelendők a proinflammatoricus citokinek (például IL1, IL6, tumornekrózisfaktor-α [TNFα]), chemokinek (például IL8), mátrixmetalloproteináz enzimek, prosztaglandinok, leukotriének, reaktívoxigén-gyökök [22]. A leukocyták által termelt citokinek a vascularis endotheliumot is aktiválják.…”
Section: A Köszvényes Gyulladás Patogenezise: Inflammasomaaktiváció éunclassified